Risk of adenomyosis according to the type of previous uterine surgery - Gamze Yilmaz; Emre Erdem Tas; Ayse Filiz Yavuz (Medicine Science, 2019)
This study aimed to ascertain whether previous uterine surgery has a role in the etiology of adenomyosis; to determine the incidence of uterine surgery in adenomyosis cases; and to assess the risk of adenomyosis according to the type of uterine surgery. The study included 1481 patients who had a hysterectomy due to any indication in a single center between January 2004 and December 2014. It was approved by the Ethical Rewiew Board of Ankara Yildirim Beyazit University Faculty of Medicine. Patients with and without adenomyosis were divided into two groups and compared according to age, parity, and history of previous uterine surgery. Previous uterine surgeries were also separately compared. A p-value less than 0.05 was considered statistically significant.We found that 63.4% of adenomyosis patients and 40.6% of non-adenomyosis patients underwent at least one uterine surgery. In patients with similar age and parity, those who underwent a uterine surgery were 2.494 times more at risk of being diagnosed with adenomyosis. A separate analysis of surgeries showed that previous myomectomy and Dilatation and Curetege were associated with an increased risk of adenomyosis while Cesarean-section had no significant effect. It was observed that previous uterine surgeries increase the risk for adenomyosis. Patients who had one more uterine surgery were more likely to develop adenomyosis. [Med-Science 2019; 8(1.000): 72-6]